Oxidative foliar photo-necrosis produced by the bacteria Pseudomonas cedrina - Guillermo Mendoza (Electronic Journal of Biotechnology, 2020)
Background: Although bioactive metabolites capable of causing oxidative photo-necrosis in plant tissues have been identified in fungi, little is known about this type of mechanism in bacteria. These metabolites act as photosensitizers that generate reactive oxygen species (ROS) capable of causing damage to cells. In addition, these metabolites can pass into an energetically excited state when they receive some luminous stimulus, a condition in which they interact with other molecules present in the environment, such as molecular oxygen (O2), also known as triplet oxygen (3O2), generating ROS. Results: The suspension of the bacterial culture of Pseudomonas cedrina was shown to produce foliar necrosis in papaya leaves (Carica papaya L.) only in the presence of sunlight, which is evidence of photosensitizing mechanisms that generate singlet oxygen (1O2). From the chemical study of extracts obtained from this bacteria, 3-(4-(2-carboxipropyl) phenyl) but-2-enoic acid (1) was isolated. This compound, in the presence of light and triplet oxygen (3O2), was able to oxidize ergosterol to its peroxide, since it acted as a photosensitizer producing 1O2, with which it was corroborated that a photosensitization reaction occurs, mechanism by which this bacterium could prove to cause oxidative foliar photo-necrosis. Conclusions: P. cedrina was able to induce oxidative foliar photo-necrosis because of its potential ability to produce photosensitizing metabolites that generate singlet oxygen in the plants it colonizes. Based on the above, it can be proposed that some bacteria can cause oxidative foliar photo-necrosis as an important mechanism in the pathogenesis of host species.How to cite: Mendoza G, Sánchez-Tafolla L, Trigos A. Oxidative foliar photo-necrosis produced by the bacteria Pseudomonas cedrina. Electron J Biotechnol 2020;44. https://doi.org/10.1016/j.ejbt.2020.01.007 Keywords: 3-(4-(2-carboxipropyl) phenyl) but-2-enoic acid, Bacterial oxidative foliar photo-necrosis, Carica papaya L., Foliar necrosis, Oxidative photo-necrosis, Papaya leaves, Photosensitizer, Photosensitizing metabolites, Pseudomonas cedrina, Reactive oxygen species, Singlet oxygen